Optimizing Medical Waste Management in Primary Healthcare A Hands-On Workshop for Safer and Sustainable Practices - Kurniawati, Kharisma Ayu; Augist, Rahma Nuril; Ailsa Sahda Septi Cahyarani, Ailsa Sahda Septi Cahyarani; ‘Aini, Melati Saharatu; Alhamid, Naziha Nazlah; Humairo, Mika Vernicia (Inovasi Lokal, 2025)
The management of medical waste in primary healthcare facilities is a critical issue due to its potential impact on public health and the environment. Improper handling of medical waste can lead to the spread of infectious diseases, environmental pollution, and risks to healthcare workers and communities. However, many primary healthcare facilities, particularly in developing countries, face challenges such as inadequate infrastructure, insufficient training, and limited resources. This workshop aimed to address these gaps by using role-playing simulations to provide healthcare workers with practical knowledge and skills in managing medical waste. Participants were divided into groups to simulate scenarios involving waste segregation, storage, transportation, and coordination among stakeholders. The results highlighted the importance of proper waste classification, effective communication, and the use of technology to improve efficiency. Participants also identified key challenges, such as limited storage facilities and poor coordination, and proposed practical recommendations, including regular training, increased infrastructure, and digital tracking systems. This workshop demonstrated that structured interventions can enhance medical waste management practices, ensuring safer healthcare environments and better compliance with international standards.